Implementasi Metode Enhanced Audio Steganogafi (EAS) Untuk Penyembunyian Text Terenkripsi Algoritma Gost - Selamat G M Siregar (STMIK Budi Darma, 2021)
Audio files in the Mp3 format are used as cover media. To be able to insert a secret message into the container media requires a method that can modify the object into a new object with confidential information in it without any noticeable changes from the initial object. The method used in this study is the EAS (Enhanced Audio Steganography) method and to encrypt the message using the GOST algorithm. EAS (Enhanced Audio Steganography) which is a method for inserting an encrypted message first to strengthen a secret message and then inserting it into an audio file. Encryption is done on the message using the GOST algorithm. The GOST method is a block cipher algorithm developed by a Soviet national. GOST is an abbreviation of